(untitled) (European Journal of Pure and Applied Mathematics, 2011)
We define a generalized differential and integral operators on the class A of analytic functions f(z) = z +P1n=2anzn in the unit disk U:= z2C:|z| <1 involving k−th Hadamard product (convolution) as follows Dk,f(z) = z +1X n=2 [(n − 1)( − ) + n]kanzn, (z 2 U). These operators are generalized for some of well known operators for example Sˇalˇagean operator. New classes containing these operators are investigated. Characterization and other properties of these classes are studied.